A fast track to employment and profit? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The ?Fast Track? programme in Zimbabwe has redistributed land to landless people, in order to give them the opportunity to make a living from agriculture. This report features two young recipients of land, who describe the difficulties they have faced, and the potential they see for their future as farmers.